StadtWildTiere – added value and impact of transnational urban wildlife community science projects - Geiger, Madeleine; Taucher, Anouk Lisa; Gloor, Sandra; Lauper, Mirco; Kiefer, Sarah; Kimmig, Sophia E.; Siebert, Janette; Walter, Theresa; Zink, Richard; Bontadina, Fabio; Hegglin, Daniel (Frontiers in Ecology and Evolution, 2024)
We present and exemplify the potential of the long-term community science (=citizen science) project StadtWildTiere (German for 'urban wildlife') in a transnational context. StadtWildTiere gathers opportunistic sightings of urban wildlife to raise awareness of, increase knowledge of, and promote biodiversity in urban areas across Central Europe. Transnationally similar methodologies enable direct comparisons concerning occurrence, distribution, and trends of urban wildlife populations and allow for new insights into and potential conservation and management measures of these otherwise unmonitored wildlife populations. We advocate the use and promotion for such community-based science projects, which align with the guiding principles of awareness, knowledge, and action. Such projects should whenever possible connect with similar initiatives in other countries to benefit from comparisons and get a strong impact on a transnational level.